CFD modelling and analysis of the trajectory and behaviour of oil pollutant particles in the ghanaian territorial waters - Uba, Felix; Fiagbe, Yesuenyeagbe A.K.; Opoku, Richard (Scientific African, 2020)
Petroleum activities like production, transportation and storage have placed Ghanaian waters among zones negatively impacted by human activities. These places are occupied by human occupations and its associated risks. Oil pollution in the environment affects biota and degrades human health. Predictive and descriptive tools have made the assessment of this situation possible for water quality management. In addition, these tools help in contingency planning in dealing with potential threats in the environment. In this research, the MOHID hydrodynamic numerical model was used to render forecast capacity for the possibility of finding susceptible areas to spilled oil particles in the Ghanaian waters from human activities around the region. The concept of nesting domains was used to reduce the cost and processing time (i.e. CPU) time, for computation. The hydrodynamics was modelled under three levels and validated with an average deviation of 14.00% and correlation factors above 0.80 from measured results. To locate possible shorelines susceptible to oil particles, random locations and oil exploration sites were used as discharge points for the simulations. In all, about 8 locations were included for the research and they are as follows: (2.9 oE, 4.4oN), (1.7oE, 4.6oN), (0.9oE, 4.9oN), (0.9oE, 4.6oN), (0.3oE, 5.2oN), (0.3oE, 4.6oN), (0.5oE, 5.5oN) and (0.5oE, 4.6oN). In conclusion, it took the oil particles 2 days, 6 hours; 1 day, 17 hours; 3 days; 4 days; 1 day; 4 days, 1 hour; and 22 hours for the first seven locations to get beached at the shore. For particles located at (0.5oE, 5.5oN), they were beached outside the Exclusive Economic Zone (EEZ) of Ghana. The study has revealed that the territorial waters of Ghana acts as beaching sites for oil pollutants independent of the discharge location.
Keywords: Oil production; trajectory and fate of oil spill; MOHID hydrodynamic model; forecast capacity; ACE: Energy and Environmental Sustainability; University of Energy & Natural Resources; Power; Ghana